A Selective Inhibitor of Human C-reactive Protein Translation Is Efficacious In Vitro and in C-reactive Protein Transgenic Mice and Humans - Nicholas R Jones; Melissa A Pegues; Mark A McCrory; Walter Singleton; Claudette Bethune; Brenda F Baker; Daniel A Norris; Rosanne M Crooke; Mark J Graham; Alexander J Szalai (Elsevier, 2012)
Observational studies of patients with established rheumatoid arthritis (RA) document a positive correlation between C-reactive protein (CRP) blood concentration and worsening of RA symptoms, but whether this association is causal or not is not known. Using CRP transgenic mice (CRPTg) with collagen-induced arthritis (CIA; a rodent model of RA), we explored causality by testing if CRP lowering via treatment with antisense oligonucleotides (ASOs) targeting human CRP mRNA was efficacious and of clinical benefit. We found that in CRPtg with established CIA, ASO-mediated lowering of blood human CRP levels improved the clinical signs of arthritis. In addition, in healthy human volunteers the ASO was well tolerated and efficacious i.e., treatment achieved significant CRP lowering. ASOs targeting CRP should provide a specific and effective way to lower human CRP levels, which might be an effective therapy in patients with established RA.